2020
DOI: 10.1002/pon.5290
|View full text |Cite
|
Sign up to set email alerts
|

Use of antidepressants in women after prophylactic bilateral oophorectomy: A Danish national cohort study

Abstract: Objective: To investigate the association between prophylactic bilateral oophorectomy and use of antidepressants in women with a family history of cancer.Methods: Nationwide population-based cohort study using Danish National Registries including women oophorectomized due to a family history of cancer (n = 2,002) and an age matched reference group (n = 18,018). Analyses were stratified by age at time of bilateral oophorectomy and use of hormone replacement therapy (HRT).Results: Women oophorectomized at age ≤ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Among nurses who reported no HT use at baseline, depression was more common in nurses who underwent bilateral oophorectomy. Previous studies have reported inconsistent findings in the association between oophorectomy, HT use and depression; either no effect modification by HT use 11,12 or an increased risk of depression in HT users following premenopausal oophorectomy 23,48 . However, since our measures of HT use were limited to baseline, we cannot conclude that HT use after oophorectomy is protective against depression.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Among nurses who reported no HT use at baseline, depression was more common in nurses who underwent bilateral oophorectomy. Previous studies have reported inconsistent findings in the association between oophorectomy, HT use and depression; either no effect modification by HT use 11,12 or an increased risk of depression in HT users following premenopausal oophorectomy 23,48 . However, since our measures of HT use were limited to baseline, we cannot conclude that HT use after oophorectomy is protective against depression.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies have reported inconsistent findings in the association between oophorectomy, HT use and depression; either no effect modification by HT use 11,12 or an increased risk of depression in HT users following premenopausal oophorectomy. 23,48 However, since our measures of HT use were limited to baseline, we cannot conclude that HT use after oophorectomy is protective against depression. It is also possible that there are non-hormonal explanations for the associations between bilateral oophorectomy and depression.…”
Section: Discussionmentioning
confidence: 99%